Design and Stability Analysis of a proposed Microgrid for on Campus Diesel and Photovoltaic Power Sources: Microgrid for Islanding Mode - Khan, Muhammad Iftikhar; Amir, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Pakistan is currently facing an energy crisis that is detrimental to its growth. Due to persistent load shedding by the National Grid throughout the country, the latest trend is tilting towards generating power at localized level through a mix of renewable and conventional energy sources. Such a mixture is referred to as Distributed Energy Resource (DER). Part of such a DER (i.e. solar energy) is free as naturally and mostly available in Pakistan having no degradation problem while providing benefit to the locality. The idea of using a Microgrid for our local power needs morphed accordingly. In this paper, a Microgrid design for our local campus i.e. University of Engineering & Technology, Peshawar, KPK is proposed. Our campus generators are not interconnected. Consequently, even while servicing small load periods, all of our campus’s diesel generators run at full capacity at the same time. Such a behavior is uneconomical, unacceptable and the generators run at low efficiency during islanding from the main utility grid. It is seen that behavior as such is endemic throughout Pakistan. Through design and analysis, it is proposed that if a Microgrid of such unconnected resources on campus is formed then during islanding, all generators and our Photovoltaic (PV) systems will economically and efficiently feed their common loads through load sharing. Synchronization, load flow analysis, short circuit analysis, harmonic analysis, transient stability, cost and reliability of our proposed Microgrid is analyzed using ETAP (Electrical Transient Analyzer Program) in this paper.